2011
DOI: 10.1039/c1cc15501f
|View full text |Cite
|
Sign up to set email alerts
|

Wilkinson's iridium acetate trimer as a water-oxidation catalyst

Abstract: The catalytic water-oxidation activity of Wilkinson's iridium acetate trimer (1) has been characterized electrochemically and by using chemical oxidants. We show that 1 can function as an operationally homogeneous water-oxidation catalyst when driven with sodium periodate as a primary oxidant, but rapidly decomposes using Ce(IV) as a primary oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
(21 reference statements)
1
28
0
Order By: Relevance
“…kinetic and spectroscopic data obtained when driving WO by 1 with periodate can thus be employed to understand its WO mechanism. 35 Fig. 5 shows that the WO rate is first order with respect to the concentration of 1, which in conjunction with Fig.…”
Section: Kinetic Characterization Of Wo By µ-O-µ-(so 4 )-[(Tpa)fe] 2 ...supporting
confidence: 70%
See 1 more Smart Citation
“…kinetic and spectroscopic data obtained when driving WO by 1 with periodate can thus be employed to understand its WO mechanism. 35 Fig. 5 shows that the WO rate is first order with respect to the concentration of 1, which in conjunction with Fig.…”
Section: Kinetic Characterization Of Wo By µ-O-µ-(so 4 )-[(Tpa)fe] 2 ...supporting
confidence: 70%
“…27 Use of sodium periodate has allowed for the improved characterization of a number of Ir-based WOCs due to its relatively low overpotential and the wide pH range over which it functions. [35][36][37][38][39][40][41][42] However, care must be taken when using sodium periodate to drive WO, as it can easily serve as an oxotransfer agent, and in theory could serve as the sole source of any oxygen production observed. 43,44 Nevertheless, careful study with sodium periodate allows for a more thorough understanding of the catalytic mechanism of WOCs, in turn aiding the design of WOCs with improved reactivity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…The NPs from 17 and 18 are distinct from classic, acid-insoluble IrO 2 NPs (vide infra), as they dissolve in acid 16 and re-form particles when placed in alcohol. 21,62 The λ max of the blue solutions derived from 3, 4, and 6 and the dissolved NPs, though, all differ slightly. 21 This suggested to us that the color of the solutions might be derived from molecular Ir IV species that retained their respective chelate ligands.…”
Section: Homogeneous Regime: the Stabilizing Effect Of Chelate LImentioning
confidence: 97%
“…Under these more mild conditions, Wilkinson's iridium acetate trimer was shown to evolve oxygen without forming nanoparticles. 46 Cp*Ir-based WOCs were also suggested to form catalytically active nanoparticles when driven with CAN. 16 Driving the Cp*Ir WOCs with sodium periodate showed that the bulk of the catalyst remained homogeneous after catalysis by allowing for the recovery and NMR characterization of the WOC.…”
Section: Cerium(iv)mentioning
confidence: 99%